A qualitative approach to explaining the mechanism of ion acceleration by an electron beam in plasma - Cherenshchykov, S.A. (Вопросы атомной науки и техники, 2018)
Acceleration of ions in a vacuum discharge, accompanied by electron beam, is known. Recently this effect is probably observed in connection with investigation of a high current non-sputtering magnetron discharge. In the present note a qualitative approach in the framework of a one-dimensional model of this phenomenon is considered without taking into account collisions. A high-current electron beam, when injected into the plasma, generates power oscillations. With the loss of energy for the excitation of oscillations and in the process of increasing the current of the electron beam, a virtual cathode appears. The ions are captured by the virtual cathode and accelerated in the direction of the electron collector.